HCV reinfection rates after cure or spontaneous clearance among HIV‐infected and uninfected men who have sex with men. (22nd December 2020) - Adu, Prince A.; Rossi, Carmine; Binka, Mawuena; Wong, Stanley; Wilton, James; Wong, Jason; Butt, Zahid A.; Bartlett, Sofia; Jeong, Dahn; Pearce, Margo; Darvishian, Maryam; Yu, Amanda; et al.
Abstract: Background & Aims: Hepatitis C virus (HCV) reinfection among high‐risk groups threatens HCV elimination goals. We assessed HCV reinfection rates among men who have sex with men (MSM) in British Columbia (BC), Canada. Methods: We used data from the BC Hepatitis Testers Cohort, which includes nearly 1.7 million individuals tested for HCV or HIV in BC. MSM who had either achieved sustained virologic response (SVR) after successful HCV treatment, or spontaneous clearance (SC) and had ≥1 subsequent HCV RNA measurement, were followed from the date of SVR or SC until the earliest of reinfection, death, or last HCV RNA measurement. Predictors of reinfection were identified by Cox proportional modelling. The earliest study start date was 6 November 1997 and latest end date was 13 April 2018. Results: Of 1349 HCV‐positive MSM who met the inclusion criteria, 493 had SC while 856 achieved SVR. 349 (25.65%) had HIV coinfection. We identified 98 reinfections during 5203 person‐years (PYs) yielding a reinfection rate of 1.88/100PYs. The reinfection rate among SC (2.74/100PYs) was more than twice that of those with SVR (1.03/100 PYs). Problematic alcohol use (aHR 1.73, 95% CI 1.003‐2.92), injection drug use (aHR 2.60, 95% CI 1.57‐4.29) and HIV coinfection (aHR 2.04, 95% CI 1.29‐3.23) were associated with increased risk of HCV reinfection. Mental health counselling history (aHR 0.24, 95% CI 0.13‐0.46) was associated with reduced HCV reinfection risk. Conclusions: There is the need to engage MSM in harm reduction and prevention services following treatment to reduce reinfection risk.